Characteristics retinometry pre and post cataract surgery on senile cataract patients in Sanglah Hospital, Bali-Indonesia - Ni Made Ari Suryathi; Wayan Gede Jayanegara; Ida Bagus Putra Manuaba (Intisari Sains Medis, 2020)
Background: WHO, with program Vision 2020-the Right to Sight, has a responsibility to control the most cause of blindness, which is a cataract. General-purpose of this research is to identify the retinometry pre and post cataract surgery on senile cataract patients.Method: This study design is an analytical cross sectional study. All data were collected retrospectively from the medical report of retinometry of pre and post cataract surgery in Sanglah General Hospital.Results: A total number of 60 eyes from 59 patients were included in this study. The majority of the patients were male (63.3%), aged 61-70, and came from Denpasar District (38.3%). The grading of cataract (Burrato) in this study is Burrato III (60%). A nuclear cataract is common in this study (41.7%). There were relationships between the differences of retinometry post dan pre cataract surgery with the grading of cataract (Burrato) (p<0.05), but there is no relationship with the type of cataract (p>0.05).Conclusions: There is a significant difference between retinometry pre and post cataract surgery, no significant difference between retinometry post-cataract surgery with BCVA and type of cataract. Higher grades of cataract (Burrato V) significantly correlate with higher retinometry pre and post-cataract surgery.